2005
DOI: 10.1007/s11325-005-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and ischemic heart disease in southwestern US veterans: implications for clinical practice

Abstract: This study describes associations between obstructive sleep apnea (OSA), intake of food rich in antioxidant nutrients, and ischemic heart disease (IHD) in military veterans. Subjects were male veterans (n=211), 54 to 85 years of age, and enrolled in primary care clinics at the Southern Arizona Veterans Affairs Health Care System (SAVAHCS), Tucson, AZ. Measures included the SAVAHCS Minority Vascular Center Questionnaire, the Sleep Heart Health Study Sleep Habits Questionnaire, the Arizona Food Frequency Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…1,5,7,11,17,18 Despite the growing clinical and public health concerns regarding sleep disorders, few studies have examined associations between sleep and race/ethnicity in the United States. A majority of extant racial/ethnic studies compared African Americans with and without sleep disorders, or comparing African and Caucasian Americans on sleep disordered breathing, snoring, sleep architecture, insomnia symptoms, sleep quality, daytime sleepiness, comorbid conditions, and health-related quality of life.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…1,5,7,11,17,18 Despite the growing clinical and public health concerns regarding sleep disorders, few studies have examined associations between sleep and race/ethnicity in the United States. A majority of extant racial/ethnic studies compared African Americans with and without sleep disorders, or comparing African and Caucasian Americans on sleep disordered breathing, snoring, sleep architecture, insomnia symptoms, sleep quality, daytime sleepiness, comorbid conditions, and health-related quality of life.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…S leep research over the past two decades has shown associations between sleep disorders and chronic disease, [1][2][3][4][5][6][7] poorer health-related quality of life, 8,9 increased health and work-related costs, and travel and work-related accidents. 10,11 Prevalence rates for insomnia, the most commonly reported sleep complaint, range from 20% to 40% of the population, depending on the defi ned severity and frequency, 12 and is suggested to have a bidirectional relationship with several chronic conditions including depression and cardiovascular disease.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term effects include morning headaches due to CO 2 retention, tiredness, daytime sleepiness, decreased cognitive function (thinking, memory, mood or concentration) and may involve psychomotor function that may lead to accidents in traffic and working with machines [ 10 ]. Long-term effects include hypertension, cardiomegaly, especially on the right side of the heart from pulmonary hypertension, arrhythmia from the lack of oxygen, polycythemia and ischemic heart disease [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] An association between SDB and CHD has been reported in several observational and clinic-based crosssectional studies. 6,7 However, studies on the incidence of new CHD among individuals with SDB in nonclinical populations have shown variable results. [8][9][10][11][12][13][14][15][16] In the largest longitudinal study to date, the Sleep Heart Health Study, SDB was associated with incident cardiovascular disease among men 40-70 y old with the most severe SDB (apnea-hypopnea index [AHI] ≥ 30).…”
mentioning
confidence: 99%